LncRNA LUCRC Regulates Colorectal Cancer Cell Growth and Tumorigenesis by Targeting Endoplasmic Reticulum Stress Response - Tang, Guo-Hui; Chen, Xue; Ding, Jian-Cheng; Du, Jun; Lin, Xiao-Ting; Xia, Lu; Lian, Jia-Bian; Ye, Feng; He, Xiu-Sheng; Liu, Wen (Frontiers in Genetics, 2020)
Colorectal cancer (CRC) is the second most common cause of cancer-related death worldwide, and is well known for its strong invasiveness, rapid recurrence and poor prognosis. Long non-coding RNAs (lncRNAs) have been shown to be involved in the development of variety types of cancers, including colorectal cancer. Here, through transcriptomic analysis and functional screening, we reported that lncRNA LUCRC (LncRNA Upregulated in Colorectal Cancer) is highly expressed in colorectal tumor samples and is required for colorectal cancer cell proliferation, migration and invasion in cultured cells and tumorigenesis in xenografts. LUCRC was found to regulate target gene expression of unfolded protein response (UPR) in endoplasmic reticulum (ER), such as BIP. The clinical significance of LUCRC is underscored by the specific presence of LUCRC in blood plasma of patients with colorectal cancers. These findings revealed a critical regulator of colorectal cancer development, which might serve as a therapeutic target in colorectal cancer.